Is family history still underutilised? exploring the views and experiences of primary care doctors in Malaysia - Hussein, Norita; Abdul Malik, Tun Firzara; Salim, Hani; Samad, Azah; Qureshi, Nadeem; Ng, Chirk Jenn (Springer, 2020)
Family history has long been recognised as a non-invasive and inexpensive tool to identify individuals at risk of genetic conditions. Even in the era of evolving genetic and genomic technology, the role of family history in predicting individual risk for genetic testing and guiding in preventive interventions is still relevant, especially in low-resource countries. The aim of this study was to explore primary care doctors' views and experiences in family history taking and how they utilised family history in day-to-day clinical consultations in Malaysia. Four focus group discussions and six in-depth interviews involving 25 primary care doctors were conducted. Three themes emerged from the analysis: (1) primary care doctors considered family history as an important part of clinical assessment, (2) proactive versus reactive approach in collecting family history and (3) family history collection was variable and challenging. Family history was documented in either free text or pedigree depending on the perception of its appropriateness during the consultation. This study highlighted the need to improve the approach, documentation and the implementation of family history in the Malaysian primary care settings. Integrating family filing concept with built-in clinical decision support into electronic medical records is a potential solution in ensuring effective family history taking in primary care.